2009
DOI: 10.1016/j.bone.2009.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Constrained tibial vibration does not produce an anabolic bone response in adult mice

Abstract: Osteoporosis is characterized by low bone mass and increased fracture risk. High frequency, low-amplitude whole-body vibration (WBV) has been proposed as a treatment for osteoporosis because it can stimulate new bone formation and prevent trabecular bone loss. We developed constrained tibial vibration (CTV) as a method for controlled vibrational loading of the lower leg of a mouse. We first subjected mice to five weeks of daily CTV loading (0.5 G maximum acceleration) with loading parameters chosen to independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Nevertheless, results have been controversial depending on the study design, type of individuals, and treatment, especially concerning the use of BPs 9,10 . To note, WBV proved to increase bone formation in the tibia of growing mice compared to controls 11 while it was shown inactive in adult intact mice 12 .…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless, results have been controversial depending on the study design, type of individuals, and treatment, especially concerning the use of BPs 9,10 . To note, WBV proved to increase bone formation in the tibia of growing mice compared to controls 11 while it was shown inactive in adult intact mice 12 .…”
Section: Introductionmentioning
confidence: 88%
“…This makes HF mechanical loading a powerful non-pharmacological intervention not only for the treatment or prevention of osteoporosis but also for fracture healing and beyond [1,19,20]. Numerous in vivo systems employing HF loading have been successfully used, such as whole body vibration (WBV) devices [16][17][18] and individual limb compressive loading setups [21,22]. WBV experiments have evidenced the advantageous effects of HF loading on bone [16][17][18] and on titanium implant osseointegration [23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our practice is to transport animals to the lab for daily or alternate day loading, whereas others perform loading in their animal facility. Previous data indicated that 5 weeks of daily handling and sedation induced trabecular and cortical loss in the tibia of 6-month, male C57BL/6 mice [18]. …”
Section: Introductionmentioning
confidence: 99%